Utilization of Emergent Neuroimaging for Thrombolysis‐Eligible Stroke Patients. Issue 1 (14th June 2016) - Sanossian, Nerses; Fu, Katherine A.; Liebeskind, David S.; Starkman, Sidney; Hamilton, Scott; Villablanca, J. Pablo; Burgos, Adrian M.; Conwit, Robin; Saver, Jeffrey L.
ABSTRACT: BACKGROUND: Advances in diagnostic imaging of stroke include multimodal techniques such as noninvasive angiography and perfusion imaging. We aimed to characterize trends in neuroimaging utilization among acute stroke patients. Utilization of multimodal imaging for acute stroke in the community has remained largely uncharacterized despite its increased adoption at academic medical centers. METHODS: We quantified neuroimaging utilization in the emergency department (ED) for 1, 700 hyperacute stroke patients presenting <2 hours after symptom onset who participated in the National Institutes of Health Field Administration of Stroke Therapy‐Magnesium (FAST‐MAG) study throughout Los Angeles and Orange Counties. FAST‐MAG provided no recommendation as to imaging utilization. RESULTS: A total of 1, 700 cases were imaged a median (interquartile range [IQR]) of 92 (74‐120) minutes after last known well time and 28 (19‐41) minutes after ED arrival. The initial scanner used in the ED was computed tomography (CT) in a preponderance of cases ( N = 1, 612, 95%), with magnetic resonance imaging (MRI) in 88 cases (5%). CT angiography (CTA) was obtained in 192 (11%) and perfusion CT (CTP) in 91 (5.4%) cases. MRI imaging was universally obtained using diffusion‐weighted images, 60% with MR angiography and 33% included perfusion imaging. Rates of concomitant CTA or CTP use increased in the later years of the study from 4% in 2005–2006, 2% in 2007–2008, 8% in 2009–2010, and 26% in 2011–2012 ( P for trend < .001). CONCLUSIONS: Among acute stroke patients, noncontrast CT was the most common initial imaging strategy in clinical practice in the 2005–2012 time period, though use of concomitant CTA grew to one‐quarter of cases, suggestive of an upward trend.